Ks. S. Łach, Księga Kapłańska (Poznań-Warszawa 1970); Księga Liczb (Poznań-Warszawa 1970); Księga Powtórzonego Prawa (Poznań-Warszawa 1970) - Zawiszewski, Edward (The Biblical Annals, 2017)
Book review